Authentication and authorization in microservice oriented application design. - Kovalov, Yurii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
In the past years microservice oriented design patterns obtained much popularity among the system architects and programmers. One of the obstacles in this design is authentication and authorization issues. This article presents one of the possible solutions for this problem. The essence of this methodology is a single point of authentication and many points of authorization spread across all the microservices.